CULTURAL AND EDUCATIONAL DIMENSIONS OF EU SOFT POWER - P. I. Kasatkin; N. V. Ivkina (Сравнительная политика)
The article is devoted to consideration of the specifi c «soft power»  of the European Union. As the theoretical foundations of the study  dedicated the American, Russian and European approaches to the  essence and content of «soft power» of the state, as well as other  similar concepts such as «civilian power», «normative power.» The  basic criteria of «soft power» was proposed by the founder of the conception J. Nye and by other experts. The major European countries with the greatest potential of «soft power» influence are considered to be the UK and France. They make the  greatest contribution to the process of creation of «soft power» in  the EU. The article deals with the attempts of the EU to  institutionalize the mechanisms of «soft power». The main two  criteria are cultural and educational attractiveness of Europe. The  identifi ed trends, which suggest that the cultural identity of individual European countries is falling by the wayside, represent the elements of the EU diplomacy. This is substantiated by the fact that it is a legal and regulatory framework of the European «soft power»,  that is also confi rmed by the offi cial representatives of the EU. However, as within any integration process, in the process of  «soft power» building the EU has a number of obstacles. The authors make conclusions about the prospects for the European Union to  apply the elements of «soft power», as well as the readiness of the  European countries to delegate a part of their cultural potential to the European community.